(untitled) (International journal of artificial intelligence, 2025)
This article is devoted to development of innovative technology for obtaining cellulose from cotton linnt and obtaining cellulose from cotton lint and on the basis of the development of chemical industry in the Republic of Uzbekistan. The study elaborates the optimal technological parameters for cellulose removal, analyzes its quality indicators and physicochemical properties. He also developed technology for production of carboxymethyl compositions, which are used as a stabilizing agent of drilling mixtures for oil and gas industry. The research results serve to increase cost efficiency, provide the local market with import-substituting products and create new jobs.